Percepción del desempeño tutor y la conducta agresiva. Un estudio descriptivo realizado en una I.E.P. de Comas, Lima - Carrasco Tamariz, Margarita (2014)
Descriptive research, where it is used: the questionnaire aggressive behavior AQ Buss and Perry to measure aggressive behavior, and evaluation of the tutorial and guidance of Roa and Del Río (2010). The purposes of this study were to describe the perception of tutor performance and identify the most predominant aggressive behavior in a probabilistic sample of 20 subjects in the 5th grade of Primary Education Institution in the district of Comas, Lima – Perú. The findings determined that 20% considered adequate tutor´s work, and 45% considered it as regular, in turn, the aggressive behavior with strongest presence was verbal (spreading rumors); and hostility had a minor presence.